Policy Discourse on Restructuring Work Entry and Return Hours Based on Indicative Inquiry of the Jakarta Transportation Council - Hanafiah, Hally; Hadiansah, Ihsan; Yulian, Karina (President University, 2023)
Recent data, observations and research show that the level of congestion at peak hours in Jakarta from mid-2022 to throughout 2023 has matched or even exceeded the level of congestion in 2019, or the time before the COVID-19 pandemic. One discourse to reduce the high level of congestion in DKI is the implementation of a policy to rearrange office hours in DKI and between May 22, 2023 and June 2, 2023 DTKJ conducted an indicative online questionnaire entitled